BUMDes Management Model in Improving the Community Economy in Sungai Raya Islands District, Bengkayang Regency - Anwar, Hairil; Pudjianto, Sy.; Padilah, Ahirul Habib (Universitas Tanjungpura, 2024)
This research has a purposeto describe the BUMDes Management Model in improving the community economy in Sungai Raya Islands District, Bengkayang Regency. This type of qualitative research uses a descriptive approach. Data collection uses observation techniques, interviews with village government officials and business actors from the community and documentation. Informants were determined using purposive and incidental techniques, including the Head of Karimunting Village, the Village Head of Lemungutan Island, and the BUMDes Manager of Karimunting Village and Lemungutan Island as well as the business community. Research analysis was carried out using steps according to Miles and Huberman including: data reduction, data display, and verification/drawing conclusions. The research results show that the BUMDes management model is able to improve the economy of the people of Karimunting village and Lemungutan Island village because there is a new concept that is useful for enriching the existing BUMDes management concept. The new concept is the application of a model development strategyTetrapreneur, asbreakthrough village innovation based on 4 (four pillars) of entrepreneurship, namely: Chainpreneur (Entrepreneurship Chain), Marketpreneur (Entrepreneurial Market), Qualitypreneur (Entrepreneurial Qualities, Brandpreneur (Entrepreneurial Brand).